Contribution of digitalisation for agriculture (D4Ag) in food security information system to enhance public participation - Mzini, L. B. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
This paper is based on the context of food security governance in the digital age. The paper forms part of the study (thesis) conducted by the author which evaluated the "impact of public participation of community food security projects" in Sedibeng District Municipality (SDM). The goal was to understand the level in which the public access information for food security programmes. It examines the pace of digital transformation in African agriculture and its value in food security information system to enhance public participation. An empirical approach is applied to attain the set objectives. A theoretical approach from recent research activities and Gauteng Provincial Government website is considered. The underlying development assumption is that the availability and use of reliable digital resources can enhance food security information system and influence for dissemination of information about food security programmes. The study concludes with a set of recommendations for managing food security information system for improved pro-poor.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Digitalisation for agriculture; Digital technologies; Food security governance; Food Security Information System; Public participation; Green revolution; Food security; Agricultural administration; Economic development-Citizen participation